2017
DOI: 10.7150/jca.19078
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided 125I brachytherapy for locally recurrent nasopharyngeal carcinoma

Abstract: Purpose: The study evaluated the feasibility, clinical effectiveness, and quality of life of computed tomography (CT)-guided 125 I brachytherapy for locally recurrent nasopharyngeal carcinoma (NPC). Methods: We recruited 81 patients diagnosed with locally recurrent NPC after previous radiotherapy with or without chemotherapy. Thirty-nine patients received 125 I brachytherapy (group A) and 42 received re-irradiation (IMRT, group B). The evaluated outcomes were local control, complications, and quality of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…We used cutoffs for age and recurrent tumor volume used by prior studies, which reported these as significant prognosticators. 22 - 25 To determine patterns of failure after primary RT, we fused the primary and re-RT plans. This was done via rigid registration based on bony landmarks (top of the dens, C1 to C2 vertebrae, pterygoid plates, hard palate, and the clinoid processes).…”
Section: Methodsmentioning
confidence: 99%
“…We used cutoffs for age and recurrent tumor volume used by prior studies, which reported these as significant prognosticators. 22 - 25 To determine patterns of failure after primary RT, we fused the primary and re-RT plans. This was done via rigid registration based on bony landmarks (top of the dens, C1 to C2 vertebrae, pterygoid plates, hard palate, and the clinoid processes).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, LC was superior in recurrences confined to the nasopharynx compared to those extending beyond the nasopharynx [110]. Severe late toxicity occurred in 26%, mostly in the form of nasopharyngeal necrosis, epistaxis, and headache, with no treatment-related deaths observed [112]. Intracavitary high-dose-rate BRT predominantly used to treat T2 recurrences resulted in 5-year LC and OS in 97% and 78%, respectively, with severe late toxicity occurring in 29%, predominantly as endocrine dysfunction and cranial nerve palsy [113] (Table 3).…”
Section: Brachytherapymentioning
confidence: 92%
“…Re-irradiation (overlap of the new radiation fields with the prior full-dose radiation volume) should be approached with caution in all cases, as there is a high risk of iatrogenic treatment-related morbidity and mortality [72]. Various techniques of re-irradiation have been proposed in this setting, including IMRT [17,19,20,37,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88], SRS [89][90][91], stereotactic body radiotherapy (SBRT) [91][92][93][94][95][96][97][98][99][100], proton beam therapy (PBT) [101][102][103], carbon ion radiation therapy (CIRT) [104][105][106][107][108][109], and intracavitary or interstitial brachytherapy (BRT) [110][111][112][113]…”
Section: Re-irradiationmentioning
confidence: 99%
See 2 more Smart Citations